Analysis of adherence to drug use in patients with pulmonary tuberculosis on the success of therapy at the Sigli City Health Center, Pidie Regency in 2023 - Sri Handayani; Kesaktian Manurung; Johansen Hutajulu (SEAN Institute, 2023)
Pulmonary tuberculosis is an infectious disease of the lower respiratory tract. This disease occurs due to the presence of mycobacterium tuberculosis which can be transmitted through droplets that can occur from one individual to another and form colonization in the bronchioles or alveoli. This disease if left untreated or incomplete treatment can cause dangerous complications up to death. The estimated prevalence of TB in all cases is 660,000 and the estimated incidence is 430,000 new cases per year. The number of deaths from TB is estimated at 61,000 deaths per year according to the National Strategy for Pulmonary Tuberculosis Control. What often happens that can cause failure in treatment is because the patient does not carry out instructions or in determining the right and proper treatment given by health workers to patients, it does not necessarily go well if the patient himself does not take medication properly or according to the procedure for taking the drug for pulmonary TB patients. The formulation of the problem in this study was: